2011
DOI: 10.4049/jimmunol.1001191
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive TLR7 Signaling, Type I IFN Production, and Attenuated Innate and Adaptive Immune Responses to Yellow Fever Virus in a Primate Reservoir Host

Abstract: Why cross-species transmissions of zoonotic viral infections to humans are frequently associated with severe disease when viruses responsible for many zoonotic diseases appear to cause only benign infections in their reservoir hosts is unclear. Sooty mangabeys (SMs), a reservoir host for SIV, do not develop disease following SIV infection, unlike nonnatural HIV-infected human or SIV-infected rhesus macaque (RM) hosts. SIV infections of SMs are characterized by an absence of chronic immune activation, in associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 76 publications
1
24
1
Order By: Relevance
“…This mixed cell population consisted of several cell types, only 0.4% of which were pDCs. Therefore, in this previous study (53), IFN-a may have been produced mainly by pDCs that sensed other infected blood cells through TLR7.…”
Section: Discussionmentioning
confidence: 98%
“…This mixed cell population consisted of several cell types, only 0.4% of which were pDCs. Therefore, in this previous study (53), IFN-a may have been produced mainly by pDCs that sensed other infected blood cells through TLR7.…”
Section: Discussionmentioning
confidence: 98%
“…1). Mandl and others 19 showed that the YFV-17D live-attenuated vaccine strain replicated to lower levels and for shorter duration in YFV reservoir (sooty mangabeys [Cercocebus atys]) than novel (rhesus macaques [Macaca mulatta]) hosts. Moreover, neutralizing antibody responses to YFV-17D were significantly lower in sooty mangabeys than in rhesus macaques 28 days post-infection (pi); neutralizing antibodies waned to undetectable levels by 120 days pi in sooty mangabeys but were maintained at high levels in rhesus macaques.…”
mentioning
confidence: 99%
“…Monkeys were anesthetized with ketamine at an intramuscular (i.m.) dose of 10 mg/kg body weight on day 0 of the study; and other flaviviruses 19 in NHPs and DENV vaccine candidates in humans. 23 Inocula were administered in a total volume of 1 mL, with 0.5 mL administered to each upper arm.…”
mentioning
confidence: 99%
“…This immune response involves the coordinated induction of several effector arms of innate immunity as well as adaptive immunity (10,11). Studies have suggested that the ability of YF-17D to infect dendritic cells and activate multiple Toll-like receptors may be essential for generating this potent immune response (8,(12)(13)(14). The YF-17D vaccine provides a model to study the immune response to vaccination in human populations, including both cellular and humoral responses, and to dissect the mechanisms of effective vaccine responses (10,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%